Health shocks, risk preferences and annuity choices - Johannes Hagen; Michal Hodor; Abigail Hurwitz (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2024)
This study examines the simultaneous impact of risk type and risk preferences on annuity demand. Through a quasi-experimental design that leverages individuals' reactions to their first malignant cancer diagnosis around retirement, we show that a 30% reduction in the present value of life annuities from decreased life expectancy results in just a 5% decline in annuitization rates. We further demonstrate that risk-averse individuals drive this effect, whereas the risk-tolerant remain unchanged in their demand. Our findings suggest that risk-averse individuals view life annuities as a means to ensure against longevity risk.
Keywords: G50; G52; D12; D14; 330; Annuity puzzle; Adverse selection; Advantageous selection; Health shocks